Flexible Blade‐Coated Optoelectronic Devices: Dual Functionality via Simultaneous Deposition. (20th March 2022) - Jan, Jasmine; Zhu, Juan; Ting, Jonathan; Arias, Ana C.
Abstract: Advances in printing techniques have enabled a new generation of low‐cost and large‐area flexible electronics. However, in applications where a combination of printed components is required, multiple fabrication processes and subsequent integration can be complex and time consuming. Additionally, these applications require devices to be stacked atop each other, reducing overall mechanical flexibility. In this work, surface‐energy‐patterning (SEP) is used to enable simultaneous blade coating of organic photodiode (OPD) and organic light‐emitting diode (OLED) films side‐by‐side. The result is dual functionality on a single flexible substrate. Various active layer solution concentrations are investigated to optimize active layer thicknesses and consequently optimize the performance of each device. A peak spectral responsivity of 0.33 A W −1 at 800 nm is achieved for optimized OPDs and a maximum luminance of 7000 cd m −2 is achieved for optimized OLEDs at an applied bias of 8 V. Overall, this technique enables the printing of two functionally distinct devices in a single step without compromising the performance of either device. Abstract : A simultaneous blade coating process is used to deposit organic photodiodes and organic light‐emitting diodes side‐by‐side on a single flexible substrate. Active layer solution concentrations are investigated to optimize individual device characteristics. The proposed method enables the use of a single process for dual device fabrication without compromising device performances.